Raw material composition of dispersing agent, dispersing agent as well as preparation method and application of dispersing agent

By using a specific combination of dispersants, the viscosity of the lithium iron phosphate precursor slurry is reduced, and the problems of low grinding efficiency and poor graphitization are solved, thereby achieving higher battery energy density and cycling performance.

CN119833634APending Publication Date: 2025-04-15SHANGHAI SUNRISE POLYMER MATERIAL CO LTD

Patent Information

Application Number
CN202311809524.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-26
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

During the preparation process of lithium iron phosphate, when the solid content of the precursor slurry is high, the viscosity is too high, which affects the grinding efficiency and the degree of graphitization of the product.

Method used

A dispersant is provided with a raw material composition including boric acid, polyethylene glycol, hydroxyethyl acrylate, ammonium persulfate and deionized water, and a dispersant with good dispersion properties is prepared by specific mixing and reaction steps.

Benefits of technology

On the premise of ensuring solid content, the slurry viscosity is effectively reduced, the product graphitization degree is improved, thereby improving the energy density and circulation performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004631193960000021
    Figure BDA0004631193960000021
  • Figure BDA0004631193960000031
    Figure BDA0004631193960000031
  • Figure BDA0004631193960000071
    Figure BDA0004631193960000071
Patent Text Reader

Abstract

The invention discloses a raw material composition of a dispersing agent, the dispersing agent and a preparation method and application of the dispersing agent. The raw material composition comprises the following components in parts by weight: 10-20 parts of a boron-containing compound; 0 to 30 parts of polyethylene glycol; 5 to 20 parts of an acrylic ester monomer; 0.5 to 1 part of an initiator; and 40-60 parts of an inorganic solvent, wherein the initiator is an inorganic peroxide. The dispersant provided by the invention can effectively reduce the viscosity of slurry and improve the graphitization degree of a product on the premise of ensuring the solid content.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a raw material composition of a dispersant, a dispersant and a preparation method and application thereof. Background Art

[0002] Lithium iron phosphate materials are low-priced, environmentally friendly, have long cycle life and good safety performance, and are widely used in electric vehicles, energy storage systems and other fields. Lithium iron phosphate has problems such as poor conductivity, low energy density, and low lithium ion diffusion coefficient. Currently, doping or surface coating of lithium iron phosphate is a more commonly used modification method to increase conductivity and improve cycle performance. Although the material performance has been improved to a certain extent, there is still room for optimization in the material synthesis process.

[0003] At present, the preparation process of lithium iron phosphate is mainly based on the solid phase method, and the barriers are relatively low. The solid phase method uses mechanical grinding to mix and refine the precursor particles, and uses a spray dryer to spray granulate the ground slurry. On the one hand, the lithium source, iron source, and phosphorus source are mixed evenly, and on the other hand, a loose and porous particle structure is formed to facilitate the uniform diffusion of each element in the solid phase sintering step, thereby improving the capacity and rate performance of lithium iron phosphate. Finally, carbon coating is achieved after roasting. It is characterized by simple operation, low technical barriers, and low cost, and is the choice of most lithium iron phosphate companies.

[0004] The mixing and dispersion process of lithium iron phosphate precursor is an important part of production. The dispersion and uniformity have a direct impact on the performance of the sintered material. The mechanical grinding method has the problems of low grinding efficiency and uneven particle refinement. In addition, during the precursor grinding process, due to the high viscosity, it is easy to agglomerate, resulting in low grinding efficiency, which brings difficulties to the subsequent spray drying and also affects the degree of graphitization of carbon.

[0005] Spray drying equipment has certain requirements for the viscosity of the slurry being processed. Too high slurry viscosity can easily cause nozzle blockage and low porosity of product particles. Slurries with low slurry viscosity are prone to hollow structures due to low solid content, which leads to high energy consumption and affects production efficiency. Therefore, it is crucial to appropriately increase the solid content while ensuring the appropriate slurry viscosity.

[0006] Chinese patent CN103219516A provides a method for preparing a phosphorus-boron-doped carbon-coated lithium iron phosphate material. The lithium iron phosphate material prepared by this method has sufficient grain growth, regular morphology, and exhibits excellent electrochemical properties. Chinese patent CN102504127A provides a method for synthesizing a polycarboxylic acid-based superdispersant suitable for dispersing lithium iron phosphate precursors. This dispersant can prevent the active material in the slurry from forming secondary agglomerates, and does not introduce impurity ions that are not contained in the precursor, thereby ensuring the mixing uniformity of the precursor. However, the preparation process of the dispersant is relatively complicated, and the pH value needs to be controlled and there is a certain degree of heat release, which requires temperature control. At the same time, strong oxidants are used in the preparation process, which are highly dangerous and easily produce reaction by-products. Summary of the invention

[0007] The present invention is mainly to solve the defect that when the solid content of the precursor slurry is high in the preparation process of lithium iron phosphate, the viscosity is too high, which affects the grinding efficiency and the degree of graphitization of the product, and provides a raw material composition of a dispersant, a dispersant and a preparation method and application thereof. The dispersant provided by the present invention can effectively reduce the viscosity of the slurry and improve the degree of graphitization of the product under the premise of ensuring the solid content.

[0008] In order to solve the above technical problems, the present invention provides the following technical solutions.

[0009] The present invention provides a raw material composition of a dispersant, which comprises the following components in parts by weight:

[0010]

[0011] In the present invention, the boron-containing compound may be a conventional boron-containing substance in the art, preferably boric acid and / or borate, more preferably boric acid.

[0012] In the present invention, the weight proportion of the boron-containing compound is preferably 12-20 parts.

[0013] In some optional embodiments, the weight proportion of the boron-containing compound may be 10 parts, 15 parts or 20 parts.

[0014] In the present invention, the weight proportion of the polyethylene glycol is preferably 21-30 parts.

[0015] In some optional embodiments, the weight proportion of the polyethylene glycol may be 20 parts, 25 parts or 30 parts.

[0016] In the present invention, the weight proportion of the acrylic ester monomer is preferably 8-18 parts.

[0017] In some optional embodiments, the weight percentage of the acrylic acid ester monomer may be 10 parts, 15 parts or 17 parts.

[0018] In the present invention, the acrylic ester monomer is preferably hydroxyethyl acrylate.

[0019] In the present invention, the raw material composition may include the following components in parts by weight:

[0020]

[0021] In the present invention, the initiator can be a substance commonly used in the art that can initiate polymerization, preferably a persulfate, such as potassium persulfate, sodium persulfate or ammonium persulfate.

[0022] In the present invention, the weight portion of the initiator is preferably 0.6-0.9 parts.

[0023] In some optional embodiments, the weight portion of the initiator may be 0.5 parts, 0.7 parts or 0.9 parts.

[0024] In the present invention, the inorganic solvent may be a conventional substance in the art capable of dissolving raw materials, preferably water, such as deionized water.

[0025] In the present invention, the weight proportion of the inorganic solvent may be 40 parts, 50 parts or 60 parts.

[0026] In the present invention, the raw material composition further comprises a carbon-forming agent.

[0027] Wherein, the carbon-forming agent is preferably one or more of sucrose, glucose, citric acid, oxalic acid, salicylic acid and activated carbon, such as citric acid.

[0028] The weight proportion of the carbon-forming agent is preferably 5-10 parts, such as 5 parts, 7 parts, 8 parts or 10 parts.

[0029] In some specific embodiments, the raw material composition consists of the following components in parts by weight: 15 parts of boric acid, 20 parts of polyethylene glycol, 15 parts of hydroxyethyl acrylate, 0.5 parts of ammonium persulfate, 40 parts of deionized water and 5 parts of citric acid.

[0030] In some specific embodiments, the raw material composition consists of the following components in parts by weight: 10 parts of boric acid, 20 parts of polyethylene glycol, 10 parts of hydroxyethyl acrylate, 0.7 parts of ammonium persulfate, 50 parts of deionized water and 10 parts of citric acid.

[0031] In some specific embodiments, the raw material composition consists of the following components in parts by weight: 20 parts of boric acid, 30 parts of polyethylene glycol, 17 parts of hydroxyethyl acrylate, 0.7 parts of ammonium persulfate, 60 parts of deionized water and 7 parts of citric acid.

[0032] In some specific embodiments, the raw material composition consists of the following components in parts by weight: 20 parts of boric acid, 25 parts of polyethylene glycol, 15 parts of hydroxyethyl acrylate, 0.9 parts of ammonium persulfate, 50 parts of deionized water and 8 parts of citric acid.

[0033] The present invention also provides a method for preparing a dispersant, which comprises the following steps: reacting the raw material composition as mentioned above to obtain the dispersant.

[0034] In the present invention, the method for preparing the raw material composition is preferably to first mix the polyethylene glycol, the acrylate monomer and the inorganic solvent, then mix them with the boron-containing compound, and finally add the initiator to obtain the raw material composition.

[0035] Preferably, stirring is also performed during the mixing process to ensure that the components are mixed evenly.

[0036] After mixing with the boron-containing compound, the mixed system is preferably heated and kept warm; the heating temperature is preferably 60°C-80°C, such as 60°C, 70°C or 80°C; and the keeping time is 30 minutes.

[0037] In the present invention, the reaction temperature may be a temperature conventionally used in the art that can polymerize the reactants, preferably 60°C-80°C, such as 60°C, 70°C or 80°C.

[0038] In the present invention, the reaction time may be the time conventionally used in the art for polymerizing the reactants, preferably 2 h to 4 h, such as 2 h, 3 h or 4 h.

[0039] The present invention also provides a dispersant, which is prepared by the above-mentioned preparation method.

[0040] The present invention also provides the use of the above-mentioned dispersant in the preparation process of the positive electrode material of the lithium ion battery.

[0041] In the present invention, the positive electrode material may be lithium iron phosphate.

[0042] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0043] The reagents and raw materials used in the present invention are commercially available.

[0044] The positive and progressive effects of the present invention are:

[0045] The dispersant provided by the present invention has good dispersing performance. When the dispersant is applied to the grinding of lithium iron phosphate precursor, the problem of high slurry viscosity, easy agglomeration and low grinding efficiency can be effectively solved. At the same time, the boron element in the dispersant can promote the improvement of the graphitization degree of carbon formation, and improve the energy density and cycle performance of the battery. The dispersant uses deionized water as a solvent and has good environmental performance. DETAILED DESCRIPTION

[0046] The preparation scheme of the present invention is further described below by specific examples, and the described examples are only a part of the embodiments of the present invention, rather than all of the embodiments. It should be understood that the embodiments described herein are only used to help understand the present invention and are not used for specific limitations of the present invention. All equivalent changes or modifications made according to the spirit and substance of the present invention should be included within the protection scope of the present invention.

[0047] The raw material portions in all examples are weight ratios.

[0048] Example 1

[0049] Add 40 parts of deionized water, 5 parts of citric acid, 20 parts of PEG2000 and 15 parts of hydroxyethyl acrylate to the reactor and stir continuously to make them evenly dissolved in the water. Slowly add 15 parts of boric acid to the reactor and stir, heat to 60°C and keep stirring for 30 minutes. Slowly add 0.5 parts of ammonium persulfate to the reactor and stir, keep warm at 60°C and stir for 3 hours to obtain the product boron-containing dispersant DB-001.

[0050] Example 2

[0051] Add 50 parts of deionized water, 10 parts of citric acid, 20 parts of PEG2000 and 10 parts of hydroxyethyl acrylate to the reactor and stir continuously to make them evenly dissolved in the water. Slowly add 10 parts of boric acid to the reactor and stir, heat to 80°C and keep stirring for 30 minutes. Slowly add 0.7 parts of ammonium persulfate to the reactor and stir, keep warm at 80°C and stir for 2 hours to obtain the product boron-containing dispersant DB-002.

[0052] Example 3

[0053] Add 60 parts of deionized water, 7 parts of citric acid, 30 parts of PEG2000 and 17 parts of hydroxyethyl acrylate to the reactor, and stir continuously to make them evenly dissolved in the water. Slowly add 20 parts of boric acid to the reactor and stir, heat to 70°C and keep stirring for 30 minutes. Slowly add 0.7 parts of ammonium persulfate to the reactor and stir, keep warm at 70°C and stir for 4 hours to obtain the product boron-containing dispersant DB-003.

[0054] Example 4

[0055] Add 50 parts of deionized water, 8 parts of citric acid, 25 parts of PEG2000 and 15 parts of hydroxyethyl acrylate to the reactor and stir continuously to make them evenly dissolved in the water. Slowly add 20 parts of boric acid to the reactor and stir, heat to 80°C and stir for 30 minutes. Slowly add 0.9 parts of ammonium persulfate to the reactor and stir, keep warm at 80°C and stir for 3 hours to obtain the product boron-containing dispersant DB-004.

[0056] Comparative Example 1

[0057] No dispersant added

[0058] Comparative Example 2

[0059] The mixture obtained by mixing boric acid and polyvinyl pyrrolidone was used as dispersion.

[0060] Comparative Example 3

[0061] The only difference from Example 1 is that boric acid is not added during the preparation of the dispersant, the dispersant is prepared, and then the boric acid, the dispersant and the lithium iron phosphate precursor are mixed.

[0062] Comparative Example 4

[0063] The only difference from Example 1 is that the amount of boric acid used is 5 parts.

[0064] Comparative Example 5

[0065] The only difference from Example 1 is that the amount of boric acid used is 25 parts.

[0066] Comparative Example 6

[0067] The only difference from Example 1 is that the amount of hydroxyethyl acrylate is 3 parts.

[0068] Comparative Example 7

[0069] The only difference from Example 1 is that the amount of hydroxyethyl acrylate is 25 parts.

[0070] Effect Example

[0071] The properties of the dispersants obtained in Examples 1-4 and Comparative Examples 1-7 were characterized:

[0072] The dispersant prepared in Example 1-4 was added to deionized water in an amount of 0.2 wt % and stirred evenly, and then iron phosphate was added so that the dispersant was fully contacted and adsorbed on the iron phosphate. After stirring for 3 minutes, a certain proportion of lithium carbonate and a carbon source were added, and the mixture was ground in a sand mill for 30-50 minutes to obtain a lithium iron phosphate precursor slurry, which was then dried into balls using a spray dryer and subjected to sintering and crushing processes to prepare a lithium iron phosphate material.

[0073] 1. Viscosity

[0074] The viscosity of the lithium iron phosphate precursor slurry was tested and recorded using a Brookfield viscometer with a No. 63 rotor and a rotation speed of 100 rpm; and the slurry was tested again after being placed for 24 hours.

[0075] 2. Degree of graphitization

[0076] The lithium iron phosphate obtained by the above method was subjected to confocal Raman spectroscopy (Renishaw) testing under the following test conditions: excitation wavelength 532nm; spectral range 50-2500cm -1 .

[0077] The effect data are recorded in Table 1:

[0078] Table 1

[0079]

[0080]

[0081] When the dispersant provided by the present invention is used in the preparation of lithium iron phosphate materials, the viscosity of the lithium iron phosphate precursor slurry can be effectively reduced, and the viscosity stability can be good, which is beneficial to the production and storage of the slurry; and the prepared lithium iron phosphate product has a high degree of graphitization, which is beneficial to the performance of the lithium iron phosphate electrical performance.

[0082] In Comparative Example 1, no dispersant was added. It can be seen that the discharge viscosity and 24h viscosity values ​​are both high, and the ID / IG value is also high, indicating that the degree of graphitization is low.

[0083] In Comparative Example 2, boric acid and polyvinyl pyrrolidone, a conventional dispersant in the art, were combined for the preparation of lithium iron phosphate precursor slurry. Although the viscosity was slightly reduced, it was still relatively high, and the viscosity stabilization effect was very poor.

[0084] The difference between Comparative Example 3 and Example 1 is that no boric acid is added during the preparation of the dispersant to obtain the dispersant, and then the boric acid and the obtained dispersant are mixed with the lithium iron phosphate precursor. It can be seen from the effect data that the viscosity reduction and viscosity stabilization effects are still not ideal, and the ID / IG value is very high.

[0085] The difference between Comparative Examples 4 and 5 and Example 1 is that the amount of boric acid used is not within the scope of the present invention. It can be seen that no matter how much or how little boric acid is used, the technical effect of the present invention cannot be achieved.

[0086] The difference between Comparative Examples 6 and 7 and Example 1 is that the amount of hydroxyethyl acrylate used is not within the scope of the present invention. It can be seen that no matter how much or how little hydroxyethyl acrylate is used, the technical effect of the present invention cannot be achieved.

[0087] Based on the slurry performance of the above samples and the Raman test results of the prepared lithium iron phosphate material, the dispersant provided by the embodiment of the present invention has good dispersibility. When the actual solid content is about 41%, the viscosity reduction and viscosity stabilization effects are significant, and the graphitization degree of carbon in the lithium iron phosphate product is also promoted.

[0088] The above descriptions are only a few embodiments of the present invention and do not limit the present invention in any form. Any equivalent changes or modifications made according to the spirit and essence of the present invention should be included in the protection scope of the present invention.

Claims

1. A raw material composition of a dispersant, characterized in that: It includes the following components in parts by weight:

2. The raw material composition of the dispersant according to claim 1, characterized in that The boron-containing compound is preferably boric acid and / or a borate, more preferably boric acid; and / or, the weight proportion of the boron-containing compound is 12-20 parts, such as 15 parts or 20 parts; and / or, the acrylic acid ester monomer is hydroxyethyl acrylate; And / or, the weight proportion of the acrylic acid ester monomer is 8-18 parts, such as 10 parts, 15 parts or 17 parts; And / or, the weight proportion of the polyethylene glycol is 21-30 parts, such as 25 parts or 30 parts.

3. The raw material composition of the dispersant according to claim 1, characterized in that The raw material composition comprises the following components in parts by weight:

4. The raw material composition of the dispersant according to claim 1, characterized in that The raw material composition further comprises a carbon former; the type of the carbon former is preferably one or more of sucrose, glucose, citric acid, oxalic acid, salicylic acid and activated carbon, such as citric acid; the weight proportion of the carbon former is preferably 5-10 parts, such as 5 parts, 7 parts, 8 parts or 10 parts; and / or, the initiator is optionally a sulfate, such as potassium persulfate, sodium persulfate or ammonium persulfate; And / or, the weight portion of the initiator is 0.6-0.9 parts, such as 0.7 parts or 0.9 parts; and / or, the inorganic solvent is water, such as deionized water; And / or, the weight proportion of the inorganic solvent is 40 parts, 50 parts or 60 parts.

5. The raw material composition of the dispersant according to claim 1, characterized in that The raw material composition is composed of the following components in parts by weight: 15 parts of boric acid, 20 parts of polyethylene glycol, 15 parts of hydroxyethyl acrylate, 0.5 parts of ammonium persulfate, 40 parts of deionized water and 5 parts of citric acid; Or, the raw material composition is composed of the following components in parts by weight: 10 parts of boric acid, 20 parts of polyethylene glycol, 10 parts of hydroxyethyl acrylate, 0.7 parts of ammonium persulfate, 50 parts of deionized water and 10 parts of citric acid; Or, the raw material composition is composed of the following components in parts by weight: 20 parts of boric acid, 30 parts of polyethylene glycol, 17 parts of hydroxyethyl acrylate, 0.7 parts of ammonium persulfate, 60 parts of deionized water and 7 parts of citric acid; Alternatively, the raw material composition is composed of the following components in parts by weight: 20 parts of boric acid, 25 parts of polyethylene glycol, 15 parts of hydroxyethyl acrylate, 0.9 parts of ammonium persulfate, 50 parts of deionized water and 8 parts of citric acid.

6. A method for preparing a dispersant, characterized in that: The method comprises the following steps: reacting the raw material composition described in any one of claims 1 to 5 to obtain the dispersant.

7. The method for preparing a dispersant according to claim 6, characterized in that: The preparation method of the raw material composition is to first mix the polyethylene glycol, the acrylate monomer and the inorganic solvent, then mix them with the boron-containing compound, and finally add the initiator to obtain the raw material composition; Preferably, stirring is also performed during the mixing process; After mixing with the boron-containing compound, the mixed system is preferably heated and kept warm; the heating temperature is preferably 60°C-80°C, such as 60°C, 70°C or 80°C; and the keeping time is 30 minutes.

8. The method for preparing a dispersant according to claim 6, characterized in that: The reaction temperature is 60°C-80°C, such as 60°C, 70°C or 80°C; And / or, the reaction time is 2h-4h, such as 2h, 3h or 4h.

9. A dispersant, characterized in that It is prepared by the preparation method described in any one of claims 6 to 8.

10. Use of the dispersant according to any one of claims 1 to 5 and 9 in the preparation process of positive electrode materials for lithium ion batteries.

Citation Information

Patent Citations

  • Polycarboxylic acid hyper-dispersant for dispersing lithium iron phosphate precursor

    CN102504127A

  • Preparation method of phosphate potential boron-doped carbon-wrapped phosphoric acid iron-lithium material

    CN103219516A

Cited By

  • Lithium iron phosphate precursor slurry additive and carbon-coated lithium iron phosphate

    CN121894633A